Budaya Politik Pemilih Milenial dalam Pemilu Serentak Tahun 2024 : Studi Kasus Kelurahan Liliba - Vinsensius Anoit; Ananias R.P. Jacob; Frans W. Muskanan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This thesis is entitled "Political Culture of Millennial Voters in the 2024 Election (Case Study of Oebobo District, Liliba Village). The problem studied is how the type of political culture of millennials in the 2024 general election in Liliba Village. The purpose of this study is to determine the type of political culture of millennials in the 2024 general election in Liliba Village. This study uses the theory of political culture from Almond and Verba. The approach in this study is quantitative with a survey method. The sampling technique used is the cluster sampling technique, namely the regional sampling technique. The total sample in this study was 99 people. The method used was through the distribution of questionnaires to millennials in Liliba Village. Based on the results of this study, it can be seen that the results of the study indicate that the political culture used in the general election followed by millennial voters, namely the political culture of Participants, has an influence on the orientation of political culture on the political culture of millennial voters in the simultaneous general election for the period 2024-2029.